2020
DOI: 10.2478/abmj-2020-0001
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Effects of Various Probiotic Products on Growth and Biofilm Formation of Clinical UPEC Strains

Abstract: AbstractUropathogenic Escherichia coli (UPEC) is the most prevalent pathogen causing urinary tract infections (UTIs). UPECs have various virulence factors such as adhesins, biofilm forming and toxin producing etc., to survive in urinary tract. Under certain circumstances probiotics are preferred for prevention and treatment of UTIs. In this study, we aimed to investigate the in-vitro effects of four different La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…Consistent with other studies, our results have shown that the inhibitory effects of CFSs of lactobacilli were found to vary depending on lactobacilli species, pathogens and concentration (11,42).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with other studies, our results have shown that the inhibitory effects of CFSs of lactobacilli were found to vary depending on lactobacilli species, pathogens and concentration (11,42).…”
Section: Discussionsupporting
confidence: 93%
“…Inconsistent with Naderi, Saud et al (2020) detected that CFSs of lactobacilli strains isolated from milk, were shown to have no inhibitory effects on multi-drug resistant Klebsiella and Shigella species; however it was shown that S. aureus, E. coli, Salmonella Paratyphi, Salmonella Typhi, Pseudomonas, Proteus, Acinetobacter strains were inhibited in the presence of CFSs (45). Gumus et al (2020) have shown that the growth and biofilm formation of clinically isolated Uropathogenic E.coli (UPECs) were inhibited in the presence of L. rhamnosus, L. fermentum, L. acidophilus and L. plantarum CFSs (42). In the present study, we found that all CFSs and all concentrations have inhibitory effect on CRK.…”
Section: Discussionmentioning
confidence: 99%
“…De-Man Rogosa-Sharpe (MRS) broth (Conda, Spain) was used on growth of Lactobacilli under anaerobic conditions at 37°C for 24 hours. Following overnight cultivation of Lactobacillus strains, supernatants were collected via centrifugation at 4000 rpm for 30 minutes at 4°C, then filtered with 0.2 μm pore size filters (12,23).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, alternative and supportive options need to be considered. There are studies that present promising results to cope with stages of infection using the antagonist relationship between probiotic microorganisms and pathogens (12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated that probiotics can interfere with the adhesion of uropathogenic E. coli (UPEC) to uroepithelial cells, which is a critical step in the development of UTIs 22 . Probiotics can also prevent the formation of biofilms by UPEC, which can increase their resistance to antibiotics and immune defenses 23 . By inhibiting the adhesion and colonization of uropathogens, probiotics can reduce the risk of UTIs 22,23 .…”
Section: Mechanisms Of Actionmentioning
confidence: 99%